Pancasila and Religious Values in Establishment of Legal Regulations - Muhammad Hoiru Nail; Made Arya Utama (University of Udayana, 2020)
In the news today (news update), Indonesia was briefly chopped off with headlines from the religion of the great enemy Pancasila. In this paper, we will discuss the relationship between Pancasila, religion and the formation of legislation. This is deliberately discussed in this paper to avoid greater mistakes especially for Indonesian people related to the relationship of religious values ??and Pancasila, as well as the relationship of religious values ??with the Formation of Laws and Regulations. This research is qualified into normative legal research that starts from the obscurity of the norms, namely Article 2 the Formation of Laws and Regulations that stated